Fundamental Limit of Plasmonic Cathodoluminescence - Schmidt, Franz-Philipp (Nano Lett, 2020)
[Image: see text] We use cathodoluminescence (CL) spectroscopy in a transmission electron microscope to probe the radial breathing mode of plasmonic silver nanodisks. A two-mirror detection system sandwiching the sample collects the CL emission in both directions, that is, backward and forward with respect to the electron beam trajectory. We unambiguously identify a spectral shift of about 8 nm in the CL spectra acquired from both sides and show that this asymmetry is induced by the electron beam itself. By numerical simulations, we confirm the observations and identify the underlying physical effect due to the interference of the CL emission patterns of an electron-beam-induced dipole and the breathing mode. This effect can ultimately limit the achievable fidelity in CL measurements on any system involving multiple excitations and should therefore be considered with care in high-precision experiments.